1988
DOI: 10.1111/j.1432-1033.1988.tb14091.x
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvic‐acid‐containing polysaccharide in the cell wall of Bacillus polymyxa AHU 1385

Abstract: Three acidic polymer fractions with molecular masses of about 16 kDa, 35 kDa and 70 kDa were isolated from lysozyme digests of N-acetylated cell walls of Bacilluspolymyxa AHU 1385 by ion-exchange chromatography and gel chromatography. These fractions, containing mannosamine, glucosamine and pyruvic acid in a molar ratio of about 1 : 1 : 1 together with glycopeptide components, were characterized as polysaccharide-linked glycopeptides with one, two and more polysaccharide chains. On the other hand, treatment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Pyruvylation of ManNAc residues present in the backbone structure seems to be a feature of many Bacillus SCWPs (9,16,46,47), possibly pinpointing an ancestral origin of this epitope that is necessary for the interaction between the SCWP and SLH domains (10,38). There is a strong correlation between the presence of the csaB gene encoding a putative pyruvyltransferase catalyzing the addition of pyruvate residues onto ManNAc and the nonco- valent anchoring mechanism via SLH domains (11).…”
Section: Discussionmentioning
confidence: 99%
“…Pyruvylation of ManNAc residues present in the backbone structure seems to be a feature of many Bacillus SCWPs (9,16,46,47), possibly pinpointing an ancestral origin of this epitope that is necessary for the interaction between the SCWP and SLH domains (10,38). There is a strong correlation between the presence of the csaB gene encoding a putative pyruvyltransferase catalyzing the addition of pyruvate residues onto ManNAc and the nonco- valent anchoring mechanism via SLH domains (11).…”
Section: Discussionmentioning
confidence: 99%
“…M. smegmatis also produces glycolipids containing 4,6-O-(1-carboxyethylidene)-3-O-methyl-Glc as a sugar moiety (25,34), which suggests that both homologues participate in the synthesis of these glycolipids. Sugar residues with a 4,6-O-(1-carboxyethylidene) group substitution have been found in carbohydrates such as extracellular polysaccharide and N-linked glycan, which are produced by some bacteria and yeasts (1,15,20,22,26). It has been shown that an increase in 4,6-O-(1-carboxyethylidene)-containing sugar residues leads to enhanced viscosity of extracellular polysaccharide from Xanthomonas sp., which alters the cell surface properties related to cellular attachment and protection from environmental stress (10).…”
Section: Discussionmentioning
confidence: 99%
“…10 It shows high degree of homology to several functionally characterized UDP-GlcNAc 2-epimerases [EC:5.1.3.14] which catalyze the interconversion between UDP-GlcNAc and UDP-ManNAc. 17 This epimerization process is independent of nicotinamide adenine dinucleotide oxidized form (NAD + ) and is critical for synthesizing bacterial ManNAc-containing CPSs (in both Gram-positive and Gram-negative bacteria 10 such as N. meningitidis 6 and Streptococcus pneumoniae types 19F and 19A), 18 cell wall polysaccharides of Bacillus species 1921 and Paenibacillus polymyxa (or Bacillus polymyxa), 22 teichoic acid linkage units of Gram-positive bacteria including Listeria monocytogenes, 23 Staphylococcus aureus H and Bacillus subtilis , 20,2427 and lipopolysaccharides. 28 It is also involved in the biosynthesis of UDP-N-acetylmannosaminuronic acid (UDP-ManNAcA) for producing ManNAcA-containing CPSs 29,30 and enterobacterial common surface antigen (ECA) in Enterobacteriaceae (Gram-negative) such as E. coli .…”
Section: Introductionmentioning
confidence: 99%